Colombian Brachiaria Network - International Center for Tropical Agriculture (2015)
The Colombian Brachiaria Network financed until 1999 by a Colombian Cattlemen Association (FEDEGAN-Fondo Nacional del Ganado), and involved as partners forage researchers from CORPOICA (Corporación Colombiana de Investigación Agropecuaria), a Colombian University, SENA and private producers. The objective of this Network was to select accessions and hybrids of Brachiaria with superior agronomic traits relative to commercial cultivars. As a follow-up to the initial agronomic evaluation, seed of selected Brachiaria accessions was multiplied in order to carry out on-station and on-farm grazing trials in different locations of Colombia.A total of 20 accessions of Brachiaria grown in 11 sites in Colombia were included in a combined analysis to define the effect of climate and soils on yield of the accessions evaluated.